Social research on the management of postpartum women with postpartum depression at the Nossa Senhora de Lourdes Maternity Hospital (Research, Society and Development, 2024)
The objective of this research is to present aspects of the management of postpartum depression at the Nossa Senhora de Lourdes Maternity Hospital. The importance of this issue raises a significant concern in relation to public health, directly affecting motherhood and children's development. To carry out the practical research, a social survey was carried out with interviews and questions and was supported by a small literature review to carry out the discussions. To carry out this research, 5 (five) semi-structured interviews were applied to the target audience of psychologists and psychiatrists. From the findings it was clear that personalizing postpartum care is extremely important, carefully considering the risk of depression. In addition, agile treatment is essential to address the symptoms of postpartum depression, aiming for the well-being of both mother and baby. Sertraline has been found to be a safe alternative for pregnant and lactating women who require psychiatric intervention.